ELEMENTS D’ORGANISATION DE L’ESPACE DU SUD DE LA BUCOVINE - DRAGOŞ BAROIU; PAUL RĂZVAN ŞERBAN (Revue Roumaine de Géographie)
Elements of space organisation in south Bucovina. Featuring original identity and a degree of coherence, the Bucovinean cultural space is tantamount to a kind of community spiritual fulfillment, unfortunately severed at regional level. We have deemed it useful and necessary to study and highlight the relationship between the local specificity and the organisation of the territory, a prerequisite for implementing efficient local and regional development policies. As a general conclusion, it appears that the south-Bucovina area has a relatively complex structure despite a kind of cultural uniformity, a historical past that stamped its mark on space organisation. Moreover, the behaviour of human communities is deeply imprinted in the collective mind, Prospective organisation should take into account the study-area’s resources, the role played by the physical and social infrastructure, the correct hierarchy of settlements (severely disturbed by the new settlements raised to urban status in 2004), as well as local, regional and national policies.